HAK-HAK KONSUMEN DALAM PEREDARAN PRODUK MAKANAN DAN MINUMAN DALAM RANGKA PERLINDUNGAN KONSUMEN - Surya Tamanbali, I Kadek; Sutaradjaya, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2013)
The paper entitled "Consumer rights in the circulation of food and beverage products in the context of consumer protection" has a goal is to understand how these rights as a consumer in the distribution of food and beverage products. The research method used in this study is a normative research, with findings that consumer rights are not only based on Article 4 of the Consumer Protection Act, but also the rights of consumers are generally accepted, in the sense that there are rights should not be violated by employers other than those provided for in article 4 of the Consumer Protection Act.
Keywords: Consumer, Distribution, Protection , Product